Facility Management in Social Housing: integration of Services for Management of College Student Housing as an opportunity for Supply Development in Italy - Alberto Fecchio; Ernesto Casara (Techne, 2012)
College Student Residences are construction works for which the State emphasizes the social relevance and disposes facilities for private investors and public operators. Structured transactions by Property Funds are growing since 2007 in order to develop Student Housing. These activities have been changing the Italian Offer Scenery. The proposed model focuses on highquality residential offer and it integrates residence with supports and services in the Student Housing itself. The Provider is the main subject for the development of this model; the Provider consists in a skilled Company that is able to take care of Business Promotion, current Contract Management, Facility Services, Student Management, and that can afford a detailed and qualified support in Architectural Planning and Design.